Dynamic Insulation Systems: Experimental Analysis on a Parietodynamic Wall. (November 2015) - Fantucci, Stefano; Serra, Valentina; Perino, Marco
Abstract: This paper shows the results of an extensive experimental campaign on a ventilated opaque double skin façade based on hollow clay bricks. The winter thermal performances of the dynamic insulated systems were investigated on two different full scale façade configurations through an experimental campaign in double climatic chamber and guarded heat flow meter apparatus. The laboratory tests on dynamic insulated façade (DIF) in both exhaust and supply configurations show respectively an effective reduction of heat losses and the capability of pre-heat the supply air passing across the ventilated external channel. The results confirm the extra insulation offered by the ventilated gap, which allows for a reduction of the wall insulation thickness, providing heat loss reduction and high level of indoor air quality in thin wall construction.